Studi Kelayakan Pembangkit Listrik Tenaga Surya Untuk Penerangan di Lokasi Ekowisata Mangrove Lembung, Desa Lembung, Kecamatan Galis, Kabupaten Pamekasan - Muhammad Kharisma Ayyubi; Ach Muhib Zainuri; Fauzan Baananto; Nurlia Pramita Sari; Wirawan Wirawan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Solar Power Plant is a photovoltaic system to convert electromagnetic energy from sunlight into electrical energy. This solar power plant is one of the recommended solutions for fulfilling electricity needs in remote rural areas where the PLN electricity network does not enter and has abundant sunlight and fuel is difficult to obtain. Based on data from the Global Solar Atlas, Lembung Mangrove Ecotourism, Galis, Pamekasan Regency has a sunlight potential of 4,603 kWh/m² per day. Therefore, it is unfortunate if this potential is not optimally utilised to build an off-grid solar power plant. The purpose of the research is to assess the feasibility of installing PLTS in Lembung Mangrove Ecotourism in terms of technical, economic, and investment feasibility analysis. From the research results, to meet the electricity demand of 15,055 kWh, it needs 12 200 Wp PV modules assembled in 6 series 2 parallel, 8 12V 200Ah batteries with 4 series 2 parallel, and 1 3 kW hybrid inverter are needed. From the simulation results, the estimated energy that can be produced is 35 kWh with a performance of the system is 61.42%. In terms of investment, the initial capital required is Rp89,954,000 so that the NPV value is obtained at Rp1,725,979, PI is 1.01, and PBP is estimated to fall in year 22 month 11.